Understanding Food Delivery Mobile Application Technology Adoption: A UTAUT Model Integrating Perceived Fear of COVID-19 - Wilert Puriwat; Suchart Tripopsakul (Emerging Science Journal, 2021)
The COVID-19 pandemic has changed people's lifestyles and catalysed digital platform adoption, including within the context of the food delivery business. During the COVID-19 pandemic, food delivery mobile applications gained numerous new users, with the industry being one of the few domains to have leveraged the pandemic's outbreak. This study investigates the factors that have influenced the adoption of food delivery mobile application technology during the pandemic in Thailand. The research model was adopted from the Unified Theory of Acceptance and Use of Technology (UTAUT) model, integrating perceived fear of COVID-19. Empirical research was conducted using data from 223 food delivery mobile application users in Thailand, with Structural Equation Modelling used to validate the model and analyse the hypotheses. The results indicate that the intention to use food delivery applications was significantly influenced by social influence, performance expectancy, effort expectancy, and perceived fear. Facilitating conditions significantly impacted actual usage behaviour, with moderating results revealing a stronger influence on behaviour intention of perceived fear of COVID-19 among females than males and among younger respondents than older respondents. The variance explained by the modified UTAUT model for intention to adopt food delivery mobile application technology was found to be 59.4%. This research makes a significant contribution to the literature in terms of validating a theory-driven framework that emphasizes the factors which impact the adoption of food delivery mobile application technology in the context of the COVID-19 pandemic. Doi: 10.28991/esj-2021-SPER-08 Full Text: PDF